2017
DOI: 10.3389/fimmu.2017.00444
|View full text |Cite
|
Sign up to set email alerts
|

The Length of N-Glycans of Recombinant H5N1 Hemagglutinin Influences the Oligomerization and Immunogenicity of Vaccine Antigen

Abstract: Hemagglutinin glycoprotein (HA) is a principle influenza vaccine antigen. Recombinant HA-based vaccines become a potential alternative for traditional approach. Complexity and variation of HA N-glycosylation are considered as the important factors for the vaccine design. The number and location of glycan moieties in the HA molecule are also crucial. Therefore, we decided to study the effect of N-glycosylation pattern on the H5 antigen structure and its ability to induce immunological response. We also decided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
2
12
0
1
Order By: Relevance
“…In most cases, only shake-flask experiments were performed, in which comparisons to other strains or impact of product glycosylation patterns can be biased, due to the uncontrolled behavior in terms of process control (e.g. pH, dissolved oxygen) [ 19 , 20 , 22 , 23 ]. In literature, environmental stressors are known to affect a protein’s post-translational processing [ 24 ], which highlights the importance of analyzing a protein’s properties during the controlled production in bioreactors.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, only shake-flask experiments were performed, in which comparisons to other strains or impact of product glycosylation patterns can be biased, due to the uncontrolled behavior in terms of process control (e.g. pH, dissolved oxygen) [ 19 , 20 , 22 , 23 ]. In literature, environmental stressors are known to affect a protein’s post-translational processing [ 24 ], which highlights the importance of analyzing a protein’s properties during the controlled production in bioreactors.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we showed that immunization with the subunit vaccine based on the extracellular region of the H5 haemagglutinin with deletion of the multibasic cleavage site elicited serum haemagglutination-inhibiting antibodies and fully protected chickens from lethal infections by the highly pathogenic H5N1 virus [9]. We also demonstrated the feasibility of producing H5N1 HA antigen in yeast [9, 10]. Therefore, testing this expression system for production of other influenza antigens, especially those HAs which are components of strains typical for humans, was successful.…”
Section: Discussionmentioning
confidence: 99%
“…The crucial issue for a vaccine to be licensed for medical use is to develop an effective process for the purification of the protein product [10]. Our work addresses both vaccine production steps: the expression and the purification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations